Hello, Earth! : poems to our planet - Sidman, Joyce (Eerdmans Books for Young Readers, 2021)
"We walk on Earth's surface every day, but how often do we wonder about the incredible planet around us? From the molten cracks below to the shimmering moon above, Hello, Earth! explores the wonders of the natural world. This playful journey across our puzzle-piece continents does not hesitate to ask questions--even of the Earth itself! ...The book concludes with extensive scientific material to foster further learning about how the earth works, from water cycles to plate tectonics to the origin of ocean tides." -- Amazon.com.